Fe-rich filamentary textures reveal timescales of magmatic interaction before the onset of high-energy explosive events at basaltic volcanoes - Claudia D'Oriano; Chiara Montagna; Simone Colucci; Paola Del Carlo; Federico Brogi; Daniele Morgavi; Alessandro Musu; Fabio Arzilli; Simone Costa; Patrizia Landi (Volcanica)
Fe-rich filamentary textures are almost ubiquitous in products from explosive eruptions at basaltic volcanoes and, in particular, they characterize the groundmass of ash and lapilli emitted during high-energy events. Here, we present a multidisciplinary study integrating petrological analyses with computational fluid dynamics simulations to propose a new mechanism responsible for their formation. Detailed textural and compositional features of Fe-rich filaments were examined in the products of explosive eruptions with different intensities from Stromboli and Etna (Italy) volcanoes. Results reveal that they represent compositional boundary layers developed at the plagioclase-melt interface in response to the interaction between magmas with different compositions and volatile contents. Numerical simulations indicate that boundary layers can detach from crystals and disperse into resident melts due to their higher density and can survive as metastable melts for some days under magmatic conditions. We suggest that Fe-rich filaments testify to the recharging of deep magma a few days before high-energy explosive events at basaltic open-vent volcanoes, even when primitive magmas are not erupted.